ANALISIS WACANA DALAM LIRIK LAGU MANDARIN KARYA JOKER XUEè–›ä¹‹è°¦ - Cindy Lestari; Septerianie Sutandi (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2023)
Discourse is the highest language unit above the clause and has sentences which are interrelated and related both semantically and contextually. The correlation in discourse can be divided into two types, the relevance of form or cohesion and the relevance of meaning or coherence. Through this research, the author will conduct a discourse analysis on the lyrics of Mandarin songs by Joker Xue (è–›ä¹‹è°¦), the objects of this research are based of Joker Xueâ€™s(è–›ä¹‹è°¦) love-relationship songs which has a similar theme. Some songs which were taken as objects for this research areã€Šè®¤çœŸçš„é›ªã€‹ ã€ã€Šä½ è¿˜è¦æˆ‘æ€Žæ ·ã€‹ ã€ã€Šæ·±æ·±çš„çˆ±è¿‡ä½ ã€‹ ä»Šç”Ÿç‰ˆ ï¼Œ and ã€Šæ¼”å‘˜ã€‹. Through this research, the author will analyze the correlation between cohesion and coherence in the lyrics of the songs by Joker Xue (è–›ä¹‹è°¦) which affects the writing style. The focus of this research is grammatical cohesion, lexical cohesion, and coherence.